Running on Empty: Of Hypopinealism and Human Seasonality - Kunz, Dieter; Wahnschaffe, Amely; Kaempfe, Nina; Mahlberg, Richard (Frontiers in Pharmacology, 2021)
The pineal hormone melatonin is the natural transducer of the environmental light-dark-signal to the body. Although the responsiveness to photoperiod is well conserved in humans, only some 25 percent of the human population experiences seasonal changes in behavior. As a consequence, humans seem to have adapted - at least partly - to the seasonal changes in day length. The aim of the study was to demonstrate that the individual melatonin deficit marker DOC (degree of pineal calcification) is related to variation of seasonal phenomena in humans. Out of 3011 patients in which cranial computer tomography (cCT) was performed for diagnostic reasons, finally 97 consecutive “healthy” subjects (43 female, 54 male; age 18–68 yrs., mean ± SD: 35.0 ± 13.1) were included. Exclusion criteria were e.g.: pathological finding in cCT, acute/chronic illness including alcohol/drug abuse, shift-work, medication known to influence melatonin excretion. Degree of pineal calcification DOC was semi-quantitatively determined using the previously validated method. The seasonal pattern assessment questionnaire (SPAQ) was performed in a telephone interview. Twenty-six subjects fulfilled criteria for seasonal affective disorder (SAD) or subsyndromal (S)-SAD. Seasonality was more pronounced in women as compared to men (SPAQ seasonality score 7.8 ± 4.0 vs. 4.9 ± 4.5; p = 0.001) and negatively and significantly associated with age (r = -0.178; p = 0.04). Subjective sleep length significantly varied between seasons (repeated measures ANOVA: F = 45.75; p < .0001) with sleep during winter being 53 min (±70 min) longer than during summer. Controlling for age total seasonality score was negatively and significantly associated with DOC (r94 = -0.214; p = 0.036). Data confirm earlier studies with respect to distribution of seasonality with sex and age. The survival of seasonality in sleep length of people living in an urban environment underlines functionality of the circadian timing system in modern societies. Moreover, data confirm for the first time, that diminished experience of seasonality in behavior is associated with a reduced individual capacity to produce melatonin.